Anansi boys - Gaiman, Neil (HarperTorch, an imprint of HarperCollins Publishers, 2005)
The name "Fat Charlie" is just one of the many embarrassing "gifts" his father bestowed on Charlie Nancy-before the old man dropped deal on a karaoke stage and ruined Fat Charlie's life. Because, you see, Charlie's dad wasn't just any dad. He was Anansi, a trickster god, the spider-god, the spirit of rebellion, able to overturn the social order, create wealth out of thin air, and baffle the devil. And he never told Fat Charlie about Spider, who shows up on his doorstep claiming to be the brother Charlie never knew, and who proceeds to make his life more interesting ... and a lot more dangerous.